Henoch-Schönlein nephritis: long-term prognosis of unselected patients. Issue 6 (June 1981) - Koskimies, O; Mir, S; Rapola, J; Vilska, J
Abstract : Progressive glomerulonephritis is the most serious feature of Henoch-Schönlein syndrome. In a series of 141 children with Henoch-Schönlein purpura 39 (28%) had abnormal urinary sediment for a duration of more than one month. This subgroup was followed up for 3.0 to 13.8 (mean 7.2) years. One child progressed to renal failure and 2 developed chronic glomerular disease. In this series most of the patients with Henoch-Schönlein syndrome and nephritis had a good prognosis.